World reimagined: Americans and human rights in the twentieth century - Bradley, Mark (Human rights in history, 2016)
"For readers who want to understand why human rights has become the moral language of our time. It explores the making of a twentieth century global human rights imagination and its American vernaculars in times of war, decolonization and globalization during the transformative decades of the 1940s and 1970s"--Provided by publisher.